Multi-Users Resource Allocation Problem in OFDM Systems Under the Underlay Spectrum Sharing Mode for Cognitive Radio - Xinbin Li; Aiwu Shi; Xingfang Song (Dianxin kexue)
In order to solve the multi-users’ resource allocation problem of OFDM systems under the underlay spectrum sharing mode conveniently and efficiently，a fair resource allocation algorithm with low complexity was proposed.The fair subcarrier allocation algorithm was applied to allocate subcarrier for cognitive users to turn the complex problem of resource allocations into a simple problem of a single user power allocation.Also a linear capped water-filling algorithm with low complexity was used to solve the subcarrier power allocation problem.Simulation results show that，compared with other methods，the proposed method has very good effectiveness and superiority in application to the TV frequency’s OFDM system.